Characteristics of non-Hodgkin lymphoma patients in Otorhinolaryngology-HNS Department Zainoel Abidin General Hospital Banda Aceh - Fadhlia Fadhlia; Benny Kurnia; Lily Setiani; Yerni Karnita; Juniar Juniar; Iip Berliananda (Oto Rhino Laryngologica Indonesiana, 2020)
Background: Non-Hodgkin’s lymphoma (NHL) is a primary malignancy in the lymphatic system and extranodal lymphoid tissue originating from B lymphocyte cells, T lymphocytes or natural killer (NK) cells. The incidence of NHL continues to increase with various characteristics. Objective: To find out the characteristics of NHL sufferers undergoing treatment in Otorhinolaryngology Head and Neck Surgery Department of dr. Zainoel Abidin Regional General Hospital (RSUDZA), Banda Aceh from January 2015 to December 2018. Method: This was an observational descriptive study conducted at Banda Aceh RSUDZA using retrospective secondary data collection from medical records that met the inclusion criteria, in total sampling method. Result: Found 32 research subjects, dominantly male (20), the highest age range was 56-65 years (10). The main complaints were neck lumps (10) and oropharynx lumps (11). The most common NHL was from B lymphocyte cells (6). The chemotherapy regimens used are cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) and rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). The most frequent side effects are anemia, hypoalbuminemia, and leukopenia. Conclusion: The results showed that NHL was most common in men with an increased incidence in the fifth decade. Neck lumps are the most common complaint. The chemotherapy regimen used is CHOP and R-CHOP.Keywords : Non-Hodgkin’s Lymphoma, chemotherapy ABSTRAK Latar belakang: Limfoma Non-Hodgkin (LNH) adalah keganasan primer pada sistem limfatik dan jaringan limfoid ekstranodal yang berasal dari sel limfosit B, limfosit T atau sel natural killer (NK). Kejadian LNH terus meningkat dengan berbagai karakteristik. Tujuan: Melihat karakteristik penderita LNH yang menjalani pengobatan di Departemen THT-KL RSUD dr. Zainoel Abidin (RSUDZA), Banda Aceh pada periode Januari 2015 sampai Desember 2018. Metode: Penelitian deskriptif observasional dengan pengambilan data sekunder secara retrospektif dari rekam medis yang memenuhi kriteria inklusi, dengan metode total sampling. Hasil: Didapatkan total subjek penelitian 32 orang, dominan pada lakilaki (20), rentang usia tertinggi antara 56-65 tahun (10). Keluhan utama terbanyak adalah benjolan di leher (10) dan benjolan orofaring (11). LNH yang berasal dari sel limfosit B paling banyak dijumpai (6). Regimen kemoterapi yang digunakan adalah cyclophosphamide, doxorubicin, vincristine, and prednisone (CHOP) dan rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP). Efek samping paling sering adalah anemia, hipoalbuminemia dan leukopenia. Kesimpulan: Hasil penelitian menunjukkan LNH paling sering pada laki-laki dengan angka kejadian meningkat pada dekade kelima. Keluhan yang paling sering adalah benjolan di leher. Regimen kemoterapi yang digunakan adalah CHOP dan R-CHOP.